Association of resistance-related protein expression with poor vascularization and low levels of oxygen in human rectal cancer - Mattern, Jürgen; Kallinowski, Friedrich; Herfarth, Christian; Volm, Manfred (International journal of cancer, 1996)
Rectal carcinomas of previously untreated patients were analyzed for oxygen status using a computerized polarographic needle electrode histograph. Microvessel density and expression of c-jun, vascular endothelial growth factor (VEGF) and several resistance-related proteins (glutathione S-transferase-π, GST; thymidylate synthase, TS; metallothioneine, MT) were determined using immunohistochemistry. To examine whether a relationship exists between intratumoral vessel density and tumor oxygenation, microvessel counts were determined in a 400× field using factor-VIII-related antigen and were correlated with the corresponding pO2 values. Linear regression analysis revealed a significant relationship between vessel density and oxygenation status of the tumors. Expression of c-jun, VEGF and resistance-related proteins was correlated with microvessel counts and pO2 values. Significantly lower vessel counts were found in GST- and MT-positive tumors and in tumors with overexpression of c-jun and VEGF than in negative tumors. In addition, significantly lower pO2 values were found in c-jun- and VEGF-positive tumors as well as a tendency for pO2 values to be lower in tumors where MT, GST and TS were expressed. These data show that expression of c-jun, VEGF, and resistance-related proteins is linked with poor vascularization and low oxygenation status in rectal cancer. © 1996 Wiley-Liss, Inc.
Elektronische Reproduktion der Druck-Ausgabe 6. Dezember 1998
Gesehen am 20.08.2025